Using action research to enhance learning on end-use energy demand: lessons from reflective practice. Issue 6 (3rd July 2017) - Petrova, Saska; Torres Garcia, Miguel; Bouzarovski, Stefan
Abstract : This paper responds to the need for a greater integration of energy and environment themes in the higher education curriculum. We explore the practical implications of empowering students towards the implementation of individual action research projects focused on investigating and addressing insufficient or wasteful energy consumption among households and businesses. The paper scrutinizes a series of teaching and assessment activities within this domain, undertaken during 6 consecutive academic years – between 2008 and 2013 – within a third-level undergraduate course unit at the University of Birmingham in the United Kingdom. Using questionnaire surveys, assessed projects and interviews with the students, we have found evidence to suggest that the action research projects contributed to the emergence of constructive alignment in the entire teaching process, while opening the space for informal action learning 'sets' leading to the generation of new problem-solving skills useful in the job market.